Plan de marketing para mejorar la fidelización de los socios de la cooperativa de ahorro y crédito Nuestra Señora del Rosario en Cajabamba - 2016 - Iparraguirre Fabian, Neil Jhandari (2017)
He present research work ; Its general objective is: Propose a marketing plan to improve the loyalty of the members of the savings cooperative Nuestra Señora del Rosario in Cajabamba 2016. For the present research report, the descriptive design was used, as well as the methods: deductiveinductive, analytical, synthetic and statistical method. In the techniques of data collection, the survey was used. According to the results obtained we have that 28.68% of the members are always loyal to the COOPAC - NSR, 30.75% indicate that almost always, 15.51% indicate that regular, 15.40% indicate that almost never and 9.66% indicate that never . The COOPAC - NSR currently does not have a marketing plan which influences the institution does not meet the specified goals in terms of recruitment and growth of new partners; for this, within the marketing plan proposal, strategies were designed to improve the relationship between associates and the institution in order to retain them and thus obtain benefits for the institution and the partners. It was determined that the marketing plan does influence the loyalty of the members of the Cooperativa de Ahorro y Crédito Nuestra Señora del Rosario. The Marketing Plan proposal has an implementation of 06 months and a budget of US $ 9,179.71.